MiR-122 Reverses the Doxorubicin-Resistance in Hepatocellular Carcinoma Cells through Regulating the Tumor Metabolism - Pan, Chenwei (PLoS One, 2016)
Doxorubicin (DOX) is one of the most commonly used anticancer drugs in the treatment of hepatoma. However, acquired drug resistance is one of the major challenges for the chemotherapy. In this study, a down-regulation of miR-122 was observed in doxorubicin-resistant Huh7 (Huh7/R) cells compared with its parental Huh7 cells, suggesting miR-122 is associated with the chemoresistance. Meanwhile, luciferase reporter assay proved that the PKM2 is the target of miR-122, and we reported that the glucose metabolism is significantly up-regulated in Huh7/R cells. Importantly, overexpression of miR-122 in Huh7/R cells reversed the doxorubicin-resistance through the inhibition of PKM2, inducing the apoptosis in doxorubicin-resistant cancer cells. Thus, this study revealed that the dysregulated glucose metabolism contributes to doxorubicin resistance, and the inhibition of glycolysis induced by miR-122 might be a promising therapeutic strategy to overcome doxorubicin resistance in hepatocellular carcinoma.